DAMPAK EKSTRAKURIKULER OLAHRAGA TERHADAP MINAT SISWA DALAM MENGIKUTI KEGIATAN OLAHRAGA - Hardiansyah Liputra (Journal of Physical Education and Sport Science, 2022)
Additional activities or activities that are carried out outside of class hours are usually called extracurricular activities. The purpose of this study was to determine the impact of sports extracurricular activities on students' interest in sports activities. This research is an Ex Post facto research. The research design used is X extracurricular to Y student interest and Z as gender. The population of this study were all students of MTs Al-Washliyah Tasikmalaya City which consisted of 18 female students and 12 male students, so that the total population obtained was 30 students. The sampling technique used is Saturated Sampling, this technique is used when all populations are used as samples in this study according to the instrument grid above, namely using a questionnaire, or more accurately a closed questionnaire with a rating scale. Based on the results of the linearity test the value of 0.012 > 0.05, the basis for decision making in the homogeneity test, namely; If the significance value (Sig) is greater than 0.05, the research data is normally distributed. it can be concluded that there is a significant relationship or impact/linearity between Sports Extracurricular Activities and Student Interest in Participating in Sports Activities.